Psychworks interactive experiences in psychology (Minn. West Pub., 1996)
Demonstration CD-ROM contains three fully interactive modules : Operant Conditioning, Child Development, and Memory Systems. It has 500 terms and definitions in a searchable glossary.
CD-ROM.
Created by West Publishing Co. in association with Intellimation.
Keywords: Psychology